Tveganja pri uvajanju umetne inteligence v delovna razmerja in možne pravne rešitve - Bagari, Sara (Delavci in delodajalci, 2023)
In recent years, various authors have pointed out the challenges posed by the use of artificial intelligence in the employment relationships, yet only recently have international, European, and national institutions begun to reflect on how to adapt and renew existing regulations as an answer to these challenges. In this regard, an appropriate legal framework at the international, European, and national level plays a crucial role in ensuring that the benefits of artificial intelligence in employment relationships outweigh the risks. The paper therefore highlights the risks posed by the use of artificial intelligence in employment relationships and analyses legal solutions in the national and European legal frameworks, pointing out possible shortcomings of existing legal instruments.
Keywords: artificial intelligence; delovna razmerje; Delovno pravo; digitalisation; digitalizacija; discrimination; diskriminacija; employment relationships; legal framework; limitless surveillance; risks; Umetna inteligenca